George of the jungle - Hoberman, David Hoberman; Websman, Sam (USA : Walt Disney Pictures [production company] ; Kuala Lumpur : Berjaya HVN [distributor])
Bigger than life, outrageously funny and loaded with eye-popping special effects. Deep in the heart of the African jungle, a baby boy is raised by gorillas. He grows up to be the hunky, heroic, yet klutsy king of the jungle, George
Story
Executive producer, C. Tad Devlin ; editor, Stuart Dadde, Roger Bondelli ; story, Dana Olsen, Audrey Wells
Brendan Fraser, Leslie Mann, Thomas Haden Church
Keywords: Animal films; Animals in motion pictures; Wildlife films